Alterations of EDEM1 functions enhance ATF6 pro‐survival signaling. (20th October 2018) - Papaioannou, Alexandra; Higa, Arisa; Jégou, Gwénaële; Jouan, Florence; Pineau, Raphael; Saas, Laure; Avril, Tony; Pluquet, Olivier; Chevet, Eric
Abstract : Activating transcription factor 6 alpha (referred to as ATF6 hereafter) is an endoplasmic reticulum (ER)‐resident glycoprotein and one of the three sensors of the unfolded protein response (UPR). Upon ER stress, ATF6 is exported to the Golgi complex where it is cleaved by the S1P and S2P proteases thus releasing ATF6 cytosolic fragment and leading to the transcription of ATF6 target genes. In this study, we performed a phenotypic small‐interfering RNA (siRNA) screening to better characterize the ER mechanisms involved in ATF6 activation upon ER stress. This revealed that silencing of ER‐degradation‐enhancing alpha‐mannosidase‐like protein‐1 (EDEM1) increased the bioavailability of ER stress‐induced ATF6 export to the Golgi complex through the stabilization of the natively unstable ATF6 protein. Moreover, we characterized a somatic variant of EDEM1 (N198I) found in hepatocellular carcinoma that alters ATF6 signaling and might provide a selective advantage to the transforming cells. Hence, our work confirms the natively unstable nature of ATF6 and links this property to potentially associated pro‐oncogenic functions. Abstract : The unfolded protein response (UPR) is a cellular stress response that is triggered by protein misfolding in the ER. A key protein involved in 'sensing' ER stress and activating UPR genes is the transcription factor ATF6. The molecular mechanisms underpinning this role remain largely elusive. Here, Chevet and co‐authors used an siRNA‐based screen to uncover functional relationships between ATF6 and mediators of ER protein quality control (ERQC). They show that silencing of an ERQC component, EDEM1, leads to enhanced activation of ATF6, providing new insight into its regulation in the ER. Intriguingly, characterisation of a mutant variant of EDEM1 linked to hepatocellular carcinoma indicates that alteration of ATF6 signalling could promote oncogenesis.